A strictly American institution: Neil O'Brien, blackface minstrelsy, and the invention of white Catholic identity. Issue 3 (October 2019) - Blake, George K.
Abstract: This article examines the politics of race, religion and nation in relation to blackface minstrelsy during the first decades of the twentieth century. Having been superseded by more modern amusements, minstrelsy was outdated as a performance genre, yet the minstrel show served as a forum for Neil O'Brien and the Knights of Columbus fraternal society to participate in the invention of a white American Catholic identity. For fraternal society members, estranged from national belonging by religious difference, these performances situated the group as proponents of an old-fashioned American tradition, structured around anti-blackness. At a time of anti-Catholic sentiment, Catholic fraternal society members gathered for minstrel performances, distancing themselves from black people and marking themselves as white Americans.